Evolutionary conservation and conversion of Foxg1 function in brain development. (5th June 2017) - Kumamoto, Takuma; Hanashima, Carina
Abstract : Among the forkhead box protein family, Foxg1 is a unique transcription factor that plays pleiotropic and non‐redundant roles in vertebrate brain development. The emergence of the telencephalon at the rostral end of the neural tube and its subsequent expansion that is mediated by Foxg1 was a key reason for the vertebrate brain to acquire higher order information processing, where Foxg1 is repetitively used in the sequential events of telencephalic development to control multi‐steps of brain circuit formation ranging from cell cycle control to neuronal differentiation in a clade‐ and species‐specific manner. The objective of this review is to discuss how the evolutionary changes in cis‐ and trans‐regulatory network that is mediated by a single transcription factor has contributed to determining the fundamental vertebrate brain structure and its divergent roles in instructing species‐specific neuronal circuitry and functional specialization. Abstract : Among the forkhead box protein family, Foxg1 is a unique transcription factor that plays pleiotropic and non‐redundant roles in vertebrate brain development. The emergence of the telencephalon at the rostral end of the neural tube and its subsequent expansion that is mediated by Foxg1 was a key reason for the vertebrate brain to acquire higher order information processing, where Foxg1 is repetitively used in the sequential events of telencephalic development to control multi‐steps of brain circuit formation ranging from cell cycle control to neuronal differentiation in a clade‐ and species‐specific manner. The objective of this review is to discuss how the evolutionary changes in cis‐ and trans‐regulatory network that is mediated by a single transcription factor has contributed to determining the fundamental vertebrate brain structure and its divergent roles in instructing species‐specific neuronal circuitry and functional specialization.